Diversidade de Candida spp. isoladas de solos de área cultivada na presença de agrotóxicos e da mata nativa adjacente: sensibilidade planctônica e de biofilmes - Maria, Gerlane Luziana de (2020)
The native forest areas are exposed to various cultivation systems due to population demand. The use of pesticides has intensified to maintain productivity in agricultural areas. Among these pesticides are antifungals drugs, especially azole derivatives, which are widely used due to their low cost and broad spectrum. These products can impact the environment, leading to soil contamination and impacting the microbiota. Therefore, the aim was to identify Candida spp. isolated from soils of cultivated area with pesticides application and adjacent native forest, as well as to investigate the planktonic and biofilm susceptibility of these yeasts to clinical and agricultural antifungals. For this, the isolates were identified by phenotypic, biochemical and molecular assays. The minimum inhibitory concentrations (MICs) of fluconazole, itraconazole, voriconazole, amphotericin B and agricultural antifungals tetraconazole and tebuconazole were determined by the broth microdilution method. The biofilm susceptibility to voriconazole, tetraconazole and tebuconazole was assessed by the XTT reduction assay. Thus, 24 strains were identified in the cultivated soil, wich were 14 C. parapsilosis sensu stricto, 5 C. albicans, 2 C. tropicalis, 1 C. fermentati and 2 C. metapsilosis. On the other hand, 22 strains were identified in native forest soil, wich were 12 C. parapsilosis sensu stricto, 5 C. albicans, 1 C. tropicalis, 3 C. fermentati and 1 C. orthopsilosis. The amphotericin B MICs and clinical and agricultural azole MICs ranged from ≤0.03 to 0.5 µg/mL, ≤0.03 to 4 µg/mL and 1 to 128 µg/mL, respectively. All strains were classified as moderate or strong biofilm-forming regardless of isolation area. The minimum inhibitory biofilm concentration (BMICs50) for voriconazole, tetraconazole and tebuconazole were found in 3/21, 10/21 and 10/21 strains, respectively, with ranged from 128 to 1024 µg/mL. In summary, the soil has a diversity of Candida spp., especially the C. parapsilosis complex. In addition one strain of C. parapsilosis sensu stricto was resistant to itraconazole and six strains of C. albicans and one strains of C. parapsilosis sensu stricto presented trailing to the azolics. All yeasts presented high potential for biofilm formation. Finally, these biofilms remained less tolerant to the agricultural antifungals tetraconazole and tebuconazole when compared to voriconazole.